ANALISIS ADAT PRA-PERKAWINAN UTAMA, MADYA DAN NISTA ADAT PEGAYAMAN SEBAGAI MEKANISME PREVENTIF PERCERAIAN DALAM PERSPEKTIF LIVING LAW DAN MASLAHAH MURSALAH - Salsabila Rivani; Sudirman Hasan; Isroqunnajah (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study aims to analyze the role of pre-marital customary practices in preventing divorce in Pegayaman Traditional Village and to examine their relevance from the perspective of living law and maslahah mursalah. This research employs an empirical legal method with a qualitative approach, focusing on understanding social practices within the community. Data were collected through in-depth interviews, observation, and documentation involving customary leaders, religious figures, and couples who have undergone the pre-marital process. The findings reveal that pre-marital customs in Pegayaman function as a preventive social mechanism by assessing the readiness of prospective couples in terms of mental, emotional, and economic aspects. Furthermore, these practices operate as living law that is socially binding and consistently implemented within the community. From the perspective of maslahah mursalah, such customs provide tangible benefits and align with the objectives of Islamic law, particularly in preserving family stability and preventing divorce. Therefore, pre-marital customs in Pegayaman can be considered an effective preventive instrument in maintaining household resilience.